In harm's way [large type] - Pearson, Ridley (Thorndike Press, 2010)
Sun Valley sheriff Walt Fleming's budding relationship with photographer Fiona Kenshaw hits a rough patch after Fiona is involved in a heroic river rescue and she attempts to duck the press. Despite her job and her laudable actions, she begs Walt to keep her photo out of the paper and avoids him when he can't. Then Walt gets a phone call that changes everything: Seattle police sergeant Lou Boldt thinks a recent murder might have a Sun Valley connection. (Bestseller)